Design of next generation high throughput satellite communication system based on beam-hopping - Chen ZHANG; Gengxin ZHANG; Xianyu WANG (Tongxin xuebao)
Beam-hopping technology provides a basis for flexible allocation and efficient utilization of satellite resources,and it is considered as a key technology of the new generation of high-throughput satellite.With the goal of service-driven,efficient utilization of resources and on-demand coverage of hot spots area,from the aspects of system architecture,communication system,working mechanism,resource allocation method and beam-hopping pattern design,user access strategy,air interface protocol design and system workflow,a top-down feasibility and technical foundation was provided for the design of a new generation of high-throughput satellite communication system based on beam hopping.Finally,it meet the requirements of flexible and mobile information service for the space-earth integration network,as well as the demand of the space-based backbone network with high reliability and large capacity transmission.